STRATEGI PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK (STUDI DI SMK DARUT TAQWA SENGONAGUNG) - Swandhono, May Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of collaborative learning strategies in improving social skills of students at SMK Darut Taqwa Sengonagung. This research uses a quasi-experimental method with a pretest-posttest control group design involving 60 students divided into experimental and control groups. The experimental group received collaborative learning treatment, while the control group used conventional learning methods. Data collection was carried out through social skills observation sheets, questionnaires, and interviews. The results showed that collaborative learning strategies were significantly effective in improving students' social skills with an N-gain value of 0.72 (high category). The improvement was seen in aspects of communication, cooperation, leadership, and conflict resolution. Statistical tests using the t-test showed significant differences between the experimental and control groups (p < 0.05). This study concludes that collaborative learning strategies can be used as an effective alternative to improve students' social skills in vocational education)